PERLINDUNGAN HUKUM PEMEGANG SAHAM MINORITAS PERSEROAN TERBATAS DITINJAU DARI UNDANG-UNDANG NOMOR 40 TAHUN 2007 TENTANG PERSEROAN TERBATAS - Evayuni Indapratiwi, Ni Made; Mahartayasa, Made (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 02, Februari 2014, 2014)
In a Incorporated Company, there are some shareholders who made up the majority shareholders and minority shareholders. Issue which is appointed is the form of legal protection for minority shareholder in incorporated company based on government law number 40 of 2007 discuss about incorporated company (Corporate Law). The methodology used in this study is normative method which is descriptively assessing the issue as a consideration to obtain a conclusion. Analysis is done by assessing the law protection for minority shareholder according to Corporate Law. The conclusion of this study is that the Corporate Law has ruled the rights of minority shareholder in forms of: personal right, derivative right, right to have investigation, right to sell back their share to other companies, pre-emptive right, right to apply for a general meeting of shareholders held, and right of shareholders to request the dissolution of the company.
Keywords: Shareholders, Minority, Incorporated Company